Tradition & taste : exploring consumers' changing attitude - Das, Gopal, active 2016 (SAGE Knowledge. Cases., 2016)
This case depicts a managerial problem faced by Tradition and Trust, a traditional sweet and snack manufacturer, which is 100 year old family business manufacturing, retailing and exporting rewri, gajjak, sweets, namkeens and other confectionery products. Like other traditional sweet and snack manufactures, they are facing the challenge of consumers' shift towards 'healthy snacking'. Moreover, brands like Haldiram's and Bikanerwala are posing a tough competition to the traditional sweet manufacturing brands. In recent years, the brand has witnessed a decline in sales. In view of the challenges posed to brand, it wants to understand the various factors influencing decline of sales and ways to redesign the strategy for sustaining its current position in the market. The case is written to illustrate how six fundamental steps of conducting a marketing research can be used to address a given managerial problem.